Cooperative Learning Model as Mathematic Concept Introduction for Early Childhood - Rohmah, Naili; Rustono, Rustono; Rifa’i, Achmad (Universitas Negeri Semarang, 2016)
The aims of the research were to find the effectiveness of the model and identify the differences in the experimental group and the control group. The research was an experimental research of the type of nonequivalent control group design. It examined the cooperative learning model in developing mathematics for early childhood. It is limited to the introduction of mathematics skills in geometry and pattern capabilities. The sampling used purposive sampling, and the number of samples in each group was 30 children. From t-test results, it was found that the mean of the pretest of 47.47 turned into 31.07, so the experimental group increased by 16.4. It was found that tcount = -14.135 with the Sig. (2 tailed) <0.05. It means that there is a difference between the pretest and posttest in the experimental group. The results of t-test of the control group show that the mean of the pretest of 42.60 turned into 31.60, so the control group increased by 11. It was found that tcount = -10.322 with the Sig. (2 tailed) <0.05. It means that there is a difference between the pretest and posttest. However, the differences shown by the increase in the mean of the control group are smaller than the increase in the experimental group.